Composite positive electrode material and preparation method and application thereof

CN116344816BActive Publication Date: 2026-11-03NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310325646.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2026-11-03
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

Existing cathode materials, after being coated with a carbon layer, suffer from reduced specific capacity and cycle performance, and also have the problem of high moisture content.

Method used

The core material is the positive electrode active material, and the carbon coating is composed of elemental sulfur and/or elemental selenium. Me2Sx and/or Me2Sex are generated through a pre-discharge reaction. Combined with the porous structure and an appropriate thickness of carbon coating, the conductivity is improved and the moisture content is reduced.

Benefits of technology

It improves the battery's discharge specific capacity, cycle performance, and safety performance, reduces surface moisture content, and enhances battery stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116344816B_ABST
    Figure CN116344816B_ABST
Patent Text Reader

Abstract

The application provides a composite positive electrode material and a preparation method and application thereof. The composite positive electrode material comprises a core and a carbon coating layer coated on at least part of the surface of the core; the core is a positive electrode active material, and the carbon coating layer comprises sulfur and / or selenium; after pre-discharge, the carbon coating layer comprises Me2S x and / or Me2Se x ; wherein Me is selected from Li or Na, and 1≤X≤8. The composite positive electrode material not only has a small surface water content, but also has excellent conductivity and excellent specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite cathode material, its preparation method, and its application, belonging to the field of secondary battery technology. Background Technology

[0002] The cathode material is a crucial component of a battery, and its performance directly impacts the overall battery performance. Current technology involves coating the surface of the cathode material with a carbon coating layer to improve its conductivity, thereby enhancing the battery's charge / discharge performance. Furthermore, the carbon coating layer isolates the cathode material from moisture and air, helping to prevent gas generation and thus improving battery safety.

[0003] However, coating the surface of the cathode material with a carbon coating layer will affect the specific capacity of the cathode material, which in turn will affect the discharge specific capacity and cycle performance of the battery.

[0004] Therefore, there is an urgent need to provide a composite cathode material that not only has low surface moisture content, but also excellent conductivity and specific capacity. Summary of the Invention

[0005] This invention provides a composite cathode material that not only has low surface moisture content, but also excellent conductivity and excellent specific capacity.

[0006] This invention provides a method for preparing a composite cathode material. This method can produce the aforementioned composite cathode material, and the preparation process is simple and suitable for widespread application.

[0007] The present invention provides a battery comprising the above-mentioned composite positive electrode material, thereby exhibiting excellent safety performance, cycle performance, and discharge specific capacity.

[0008] The present invention provides a composite cathode material, comprising a core and a carbon coating layer covering at least a portion of the surface of the core;

[0009] The core is a positive electrode active material, and the carbon coating layer includes elemental sulfur and / or elemental selenium;

[0010] After pre-discharge, the carbon coating layer of the composite cathode material includes Me2S. x and / or Me2Se x ;

[0011] Where Me is selected from Li or Na, and 1≤X≤8.

[0012] The composite cathode material described above, wherein if Me is Na, then the cathode active material has the molecular formula shown in Formula 1;

[0013] Na b1Ni c1 Fe d1 Mn e1 M f1 O g1 Formula 1;

[0014] In Equation 1, c1+d1+e1+f1=1, 0.67≤b1≤1.25, 0.15≤c1≤0.35, 0.15≤d1≤0.35, 0.25≤e1≤0.66, 0.15≤f1≤0.35, and M is a dopant element.

[0015] The composite cathode material described above, wherein if Me is Li, the cathode active material has the molecular formula shown in Formula 2;

[0016] Li b2 Ni c2 Co d2 Mn e2 L f2 O g2 Formula 2;

[0017] In Equation 2, c2+d2+e2+f2=1, 0.75≤b2≤1.45, 0.6≤c2≤0.95, 0.005≤d2≤0.2, 0.005≤e2≤0.2, 0≤f2≤0.02, and L is the dopant element.

[0018] In the composite cathode material described above, the surface of the carbon coating layer has pores with a pore size of 0.1-100 nm.

[0019] In the composite cathode material described above, the thickness of the carbon coating layer is 1-200 nm.

[0020] In the composite cathode material described above, the carbon coating layer has a mass percentage content of 0.5-15% based on the total mass of the composite cathode material.

[0021] The composite cathode material as described above, wherein the mass percentage of elemental sulfur and / or elemental selenium is 10-300% based on the total mass of the carbon coating layer.

[0022] The composite cathode material as described above, wherein the surface moisture content of the composite cathode material is 90-700 ppm.

[0023] This invention provides a method for preparing the composite cathode material as described above, comprising the following steps:

[0024] A first calcination treatment is performed on a first mixed system including positive electrode active material and carbon source to obtain intermediate positive electrode material;

[0025] The intermediate cathode material is mixed with a sulfur source and / or a selenium source to obtain a second mixed system, and the second mixed system is subjected to a second calcination treatment to obtain the composite cathode material.

[0026] In the preparation method described above, the first calcination treatment is carried out at a temperature of 650-900℃, a heating rate of 1-5℃ / min, and a time of 2-12h; and / or,

[0027] In the second calcination treatment, the temperature is 100-200℃, the heating rate is 1-5℃ / min, and the time is 0.5-12h.

[0028] The present invention provides a battery comprising the composite cathode material as described above.

[0029] The composite cathode material of the present invention comprises a cathode active material core and a carbon coating layer comprising elemental sulfur and / or elemental selenium covering at least a portion of the surface of the core. After pre-discharge, the elemental sulfur and / or elemental selenium react with the metal Me in the electrolyte to generate Me₂Sx and / or Me₂Sex. This reaction is reversible, and the reverse reaction can increase the specific capacity of the composite cathode material, thereby improving the discharge specific capacity of the battery. It is worth noting that the presence of the carbon coating layer not only reduces the surface resistance of the core, resulting in a composite cathode material with low resistivity and improved battery charge-discharge performance, but also effectively reduces the moisture content on the surface of the composite cathode material, preventing gas generation during charge-discharge and thus improving battery safety. Therefore, the composite cathode material of the present invention possesses both excellent specific capacity and conductivity, and has low surface moisture content. When applied to batteries, the composite cathode material of the present invention can improve the battery's discharge specific capacity, cycle performance, and safety performance.

[0030] The method for preparing the composite cathode material of the present invention can produce the above-mentioned composite cathode material, and the preparation method is simple to operate and suitable for widespread application.

[0031] The battery of the present invention, due to including the above-mentioned composite cathode material, has excellent cycle performance, discharge specific capacity and safety performance. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the accompanying drawings used in the description of the embodiments of the present invention or related technologies are briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 This is a SEM image of the composite cathode material in Example 1 of the present invention. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0035] A first aspect of the present invention provides a composite cathode material, comprising a core and a carbon coating layer covering at least a portion of the surface of the core;

[0036] The core is a positive electrode active material, and the carbon coating layer includes elemental sulfur and / or elemental selenium;

[0037] After pre-discharge, the carbon coating layer of the composite cathode material includes Me2Sx and / or Me2Sex;

[0038] Where Me is selected from Li or Na, and 1≤X≤8.

[0039] It is understood that the carbon coating layer of the present invention can coat the entire surface of the core or a portion of the core surface.

[0040] The composite cathode material of the present invention comprises, from the inside out, a core and a carbon coating layer.

[0041] The core material includes a positive electrode active material. In this invention, the positive electrode active material can be a metal oxide commonly used in the art as a positive electrode active material. The positive electrode active material provides metal ions to the battery, enabling the battery to perform normal charging and discharging.

[0042] The carbon coating layer can consist of only elemental sulfur, only elemental selenium, or both. The carbon coating layer is used to coat the positive electrode active material.

[0043] In this invention, pre-discharge refers to causing a chemical reaction between the composite cathode material and the electrolyte, converting the chemical energy of the composite cathode material into electrical energy. This invention does not specifically limit the form of pre-discharge, as long as it enables the conversion of the chemical energy of the composite cathode material into electrical energy.

[0044] When the carbon coating layer consists only of elemental sulfur, after pre-discharge, the elemental sulfur reacts with Me in the electrolyte to generate Me₂S. xThe reaction equation is shown in equation a; when the carbon coating layer only includes elemental selenium, after the composite cathode material undergoes anti-electrode treatment, elemental selenium will react with Me in the electrolyte to generate Me2Sex, and the reaction equation is shown in equation b; when the carbon coating layer includes both elemental sulfur and elemental selenium, after the composite cathode material undergoes anti-electrode treatment, elemental sulfur and elemental selenium will react with Me in the electrolyte to generate Me2S respectively. x and Me2Se x .

[0045]

[0046]

[0047] In this invention, Me can be either Li or Na. It is understood that when Me is Li, the core is a lithium metal oxide cathode, and the composite cathode material of this invention can be used to prepare lithium-ion batteries; when Me is Na, the core is a sodium metal oxide cathode, and the composite cathode material of this invention can be used to prepare sodium-ion batteries.

[0048] In the composite cathode material of the present invention, after pre-discharge, elemental sulfur and / or elemental selenium will undergo a reversible reaction with metal Me in the electrolyte. The reverse reaction of this reversible reaction can increase the specific capacity of the composite cathode material, thereby increasing the discharge specific capacity of the battery.

[0049] Furthermore, the presence of a carbon coating layer in the composite cathode material not only improves its conductivity, promotes electron transport between particles, and reduces surface resistance, resulting in a composite cathode material with low resistivity, but also significantly reduces the surface moisture content due to the excellent hydrophobicity of carbon. This enhances the material's air stability, preventing gas generation during charging and discharging, and thus improving battery safety. Therefore, the composite cathode material of this invention possesses both excellent specific capacity and conductivity, and has low surface moisture content. When applied to batteries, this composite cathode material can improve the battery's discharge specific capacity, cycle performance, and safety performance.

[0050] It is understood that the performance of the positive electrode active material directly affects the performance of the composite positive electrode material. Therefore, this invention can further select the positive electrode active material in order to further improve the specific capacity and conductivity of the composite positive electrode material and reduce the surface moisture content of the composite positive electrode material.

[0051] In some embodiments of the present invention, if Me is Na, then the positive electrode active material has the molecular formula shown in Formula 1;

[0052] Na b1 Ni c1 Fed1 Mn e1 M f1 O g1 Formula 1;

[0053] In Equation 1, c1+d1+e1+f1=1, 0.67≤b1≤1.25, 0.15≤c1≤0.35, 0.15≤d1≤0.35, 0.25≤e1≤0.66, 0.15≤f1≤0.35, and M is a dopant element.

[0054] In Equation 1, the value of g1 can make Na b1 Ni c1 Fe d1 Mn e1 N f1 O g1 The algebraic sum of the positive and negative valences is 0. M is a dopant element, which can be selected from at least one of Cu, Zn, Ti, Sc, V, Co, Zr, Sb, Al, Mg, K, Ga, Li, Mo, Si, Ce, and Sn. This invention does not particularly limit the morphology of the positive electrode active material shown in Formula 1; its morphology can be irregular or spherical single-crystal particles (primary particles), or secondary particles formed after the aggregation of primary particles. When the positive electrode active material has the molecular formula shown in Formula 1, the obtained composite positive electrode material can be used to prepare sodium-ion batteries, and the obtained sodium-ion batteries have superior discharge specific capacity, cycle performance, and safety performance.

[0055] In some embodiments, sodium-ion batteries can be prepared using the compound shown in Formula 1, and the resulting sodium-ion coin half-cells exhibit a power output of 17 mAg in a voltage window of 2–4.2 V. -1 The charge / discharge rate provides a discharge capacity of 130-159 mAh / g. Sodium-ion batteries can also be fabricated using the composite cathode material comprising the core shown in Formula 1 of this invention. The resulting sodium-ion coin cell exhibits a discharge capacity of 17 mA / g within a voltage window of 2–4.2 V. -1 The discharge capacity can reach 160–190 mAh / g during high-rate charging and discharging. This is because the elemental sulfur and / or elemental selenium in the composite cathode material of this invention provide capacity during the charging and discharging process of the battery, thereby increasing the discharge capacity of the battery. Specifically, calculations show that elemental sulfur provides 1675 mAh / g when it gains electrons to form Na₂S, and elemental selenium provides 678 mAh / g when it gains electrons to form Na₂Se.

[0056] In some embodiments of the present invention, if Me is Li, the positive electrode active material has the molecular formula shown in Formula 2;

[0057] Li b2 Ni c2 Cod2 Mn e2 L f2 O g2 Formula 2;

[0058] In Equation 2, c2+d2+e2+f2=1, 0.75≤b2≤1.45, 0.6≤c2≤0.95, 0.005≤d2≤0.2, 0.005≤e2≤0.2, 0≤f2≤0.02, and L is the dopant element.

[0059] In Equation 2, the value of g2 can make Li b2 Ni c2 Co d2 Mn e2 M f2 O g2 The algebraic sum of the positive and negative valences is 0. L is a dopant element, which can be selected from at least one of Ta, Nb, Ti, Fe, Sb, Al, Mg, Na, and K. This invention does not particularly limit the morphology of the positive electrode active material shown in Formula 2; its morphology can be irregular or spherical single-crystal particles, or secondary particles formed after primary particle agglomeration. When the positive electrode active material has the molecular formula shown in Formula 2, the obtained composite positive electrode material can be used to prepare lithium-ion batteries, and the obtained lithium-ion batteries have superior discharge specific capacity, cycle performance, and safety performance.

[0060] In some embodiments, lithium-ion batteries can be prepared using the compound shown in Formula 2, and the resulting lithium-ion coin half-cells exhibit a power output of 20 mAg within a voltage window of 2.5–4.25 V. -1 The charge / discharge rate provides a discharge capacity of 170-199 mAh / g. Lithium-ion batteries can also be fabricated using the composite cathode material comprising the core shown in Formula 2 of this invention. The resulting lithium-ion coin cell half-cell exhibits a discharge capacity of 20 mA / g within a voltage window of 2.5–4.25 V. -1 The discharge capacity can reach 200–220 mAh / g during high-rate charging and discharging. This is because the elemental sulfur and / or selenium in the composite cathode material of this invention contribute capacity during the charging and discharging process, thereby increasing the battery's discharge capacity.

[0061] Furthermore, when in Equation 2, 1≤b2≤1.45, 0.75≤c2≤0.95, 0.005≤d2≤0.03, 0.005≤e2≤0.02, and 0≤f2≤0.02, the obtained composite cathode material has a more superior discharge capacity.

[0062] In some embodiments of the present invention, the surface of the carbon coating layer has pores with a pore size of 0.1-100 nm.

[0063] In this invention, the surface of the carbon coating layer has pores, and elemental sulfur and / or elemental selenium are located in the pores. In some embodiments, the pores can be at least one of micropores, mesopores, and macropores. Because the surface of the carbon coating layer has pores, the surface of the composite cathode material including the carbon coating layer also has pores, and the pore size of the surface of the composite cathode material is substantially the same as the pore size of the surface of the carbon coating layer.

[0064] When the surface pore size of the carbon coating layer is 0.1-100 nm, during the charging and discharging process of the battery, this composite cathode material can react with Me in the electrolyte. + Better contact improves the electrochemical performance of the battery. Furthermore, when the pore size of the carbon coating surface is 0.1-10 nm, the electrochemical performance of the battery can be further improved.

[0065] In some embodiments of the present invention, when the thickness of the carbon coating layer is 1-200 nm, the functions of both the carbon coating layer and the core can be fully utilized, enabling the composite cathode material to possess both superior specific capacity and conductivity, and also reducing the surface moisture content of the composite cathode material. Furthermore, when the thickness of the carbon coating layer is 1-50 nm, the electrochemical performance of the battery can be further improved.

[0066] To further improve the performance of composite cathode materials, the mass percentage of carbon coating in the composite cathode material and the mass percentage of elemental sulfur and / or selenium in the carbon coating can be further selected.

[0067] In some embodiments of the present invention, when the mass percentage of the carbon coating layer is 0.5-15% based on the total mass of the composite cathode material, the functions of both the carbon coating layer and the core can be fully utilized, enabling the composite cathode material to possess superior specific capacity and conductivity, and also reducing the surface moisture content of the composite cathode material. Furthermore, when the mass percentage of the carbon coating layer is 0.5-7% based on the total mass of the composite cathode material, the performance of the composite cathode material can be further improved.

[0068] In some embodiments of the present invention, when the mass percentage of elemental sulfur and / or elemental selenium is 10-300% based on the total mass of the carbon coating layer, the composite cathode material has superior specific capacity and conductivity, and can reduce the surface moisture content of the composite cathode material.

[0069] It is understandable that when the carbon coating layer contains only elemental sulfur, the mass percentage of elemental sulfur is 10-300% based on the total mass of the carbon coating layer; when the carbon coating layer contains only elemental selenium, the mass percentage of elemental selenium is 10-300% based on the total mass of the carbon coating layer; and when the carbon coating layer contains both elemental sulfur and elemental selenium, the mass percentage of elemental sulfur and elemental selenium is 10-300% based on the total mass of the carbon coating layer.

[0070] Furthermore, based on the total mass of the carbon coating layer, when the mass percentage of elemental sulfur and / or elemental selenium is 10-100%, the performance of the composite cathode material can be further improved.

[0071] In some embodiments of the present invention, when the surface moisture content of the composite cathode material is 90-700 ppm, the composite cathode material can better prevent gas generation during the charging and discharging process when used in a battery, thereby improving the safety performance of the battery.

[0072] A second aspect of the present invention provides a method for preparing the above-mentioned composite cathode material, comprising the following steps:

[0073] A first calcination treatment is performed on a first mixed system including positive electrode active material and carbon source to obtain intermediate positive electrode material;

[0074] The intermediate cathode material is mixed with a sulfur source and / or a selenium source to obtain a second mixed system. The second mixed system is then subjected to a second calcination treatment to obtain a composite cathode material.

[0075] Specifically, a first calcination treatment is performed on a first mixed system comprising a positive electrode active material and a carbon source to form a carbon coating layer on at least a portion of the surface of the positive electrode active material, thereby obtaining an intermediate positive electrode material comprising a carbon coating layer; the intermediate positive electrode material is mixed with a sulfur source and / or a selenium source to obtain a second mixed system; the second mixed system is subjected to a second calcination treatment to fill the carbon coating layer with elemental sulfur and / or elemental selenium, thereby obtaining the composite positive electrode material of the present invention.

[0076] This invention does not impose any particular limitation on the carbon source, as long as the first calcination treatment can form a carbon coating layer on at least a portion of the surface of the positive electrode active material. In some embodiments, the carbon source may be selected from one or more of sucrose, D-glucose, fructose, polyaniline, polyacetylene, polythiophene, dopamine, sodium alginate, graphite, graphene oxide, activated carbon, soft carbon, hard carbon, and organometallic frameworks.

[0077] This invention does not particularly limit the sulfur source, as long as elemental sulfur can be formed in the carbon coating layer after the second calcination treatment. In some embodiments, the sulfur source may be selected from sublimed sulfur and / or sulfur powder. This invention does not particularly limit the selenium source, as long as elemental selenium can be formed in the carbon coating layer after the second calcination treatment. In some embodiments, the selenium source may be selected from selenium powder.

[0078] The positive electrode active material in this invention can be obtained commercially or prepared in the laboratory.

[0079] For example, the positive electrode active material shown in Formula 1 can be prepared by a method including the following steps: mixing sodium source, nickel source, iron source, manganese source and dopant element source uniformly to obtain a mixed system, and sintering the mixed system to obtain the positive electrode active material shown in Formula 1.

[0080] The sodium source can be selected from one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide; the nickel source can be selected from one or more of nickel oxide, nickel nitrate, nickel acetate; the iron source can be selected from one or more of iron oxide, iron(II,III) oxide, ferrous oxide, and iron(II,III) nitrate; the manganese source can be selected from one or more of manganese carbonate, manganese acetate, manganese(II,III) oxide, and manganese(II,III) oxide; and the doping element source can be selected from one or more of Cu, Zn, Ti, Sc, V, Co, Zr, Sb, Al, Mg, K, Ca, Li, Mo, Si, Ce, and Sn.

[0081] When the dopant source is Cu, the Cu source can be CuO; when the dopant source is Zn, the Zn source can be ZnO; when the dopant source is Ti, the Ti source can be TiO2; when the dopant source is Sc, the Sc source can be Sc2O3; when the dopant source is V, the V source can be one or more of V2O5, VO2, V2O3, and VO; when the dopant source is Co, the Co source can be cobalt acetate; when the dopant source is Zr, the Zr source can be ZrO2; when the dopant source is Sb, the Sb source can be... The source can be Sb₂O₃; when the doping element source is Al, the Al source can be one or more of Al₂O₃ and Al(OH)₃; when the doping element source is Mg, the Mg source can be one or more of MgO and Mg(OH)₂; when the doping element source is K, the K source can be one or more of KOH and K₂S; when the doping element source is Ca, the Ca source can be one or more of CaO and CaCO₃; when the doping element source is Li, the Li source can be one or more of Li₂O, LiOH, and Li₂CO₃.

[0082] When the doping element source is Mo, the Mo source can be Na2MoO4; when the doping element source is Si, the Si source can be SiO2; when the doping element source is Ce, the Ce source can be CeO2; when the doping element source is Sn, the Sn source can be one or more of SnO and Sn2O3.

[0083] In some embodiments, the positive electrode active material shown in Formula 1 can be obtained by uniformly mixing the sodium source with the carbonate-based precursor or the hydroxyl-based precursor to obtain a mixed system, and then sintering the mixed system.

[0084] In some embodiments of the present invention, during the preparation of the positive electrode active material shown in Formula 1, the sintering temperature is 800-1000℃, the heating rate is 1-5℃ / min, and the sintering time is 10-15h. Further, the sintering temperature can be 850℃, the heating rate can be 2℃ / min, and the sintering time can be 12h.

[0085] The positive electrode active material shown in Formula 2 can be prepared by a method including the following steps: a transition metal carbonate precursor is mixed uniformly with a lithium source to obtain a third mixed system; the mixed system is subjected to a first sintering treatment, and then cooled to room temperature to obtain an intermediate positive electrode active material; the intermediate positive electrode active material is mixed uniformly with a dopant element source to obtain a fourth mixed system; the fourth mixed system is subjected to a second sintering treatment to obtain the positive electrode active material.

[0086] The transition metal carbonate precursor includes Ni, Co, and Mn elements, which can be obtained commercially; the lithium source can be selected from one or more of lithium carbonate and lithium hydroxide; the doping element source can be selected from at least one of Ta source, Nb source, Ti source, Fe source, Sb source, Al source, Mg source, Na source, and K source.

[0087] When the doping element source is Ta, the Ta source can be Ta₂O₅; when the doping element source is Nb, the Nb source can be Nb₂O₅; when the doping element source is Ti, the Ti source can be TiO₂; when the doping element source is Fe, the Fe source can be one or more of FePO₄ and Fe₂O₃; when the doping element source is Sb, the Sb source can be one or more of Sb₂O₃ and Sb₂O₅; when the doping element source is Al, the Al source can be one or more of Al₂O₃ and Al(OH)₃; when the doping element source is Mg, the Mg source can be one or more of MgO and Mg(OH)₂; when the doping element source is Na, the Na source can be one or more of NaOH, Na₂S, and Na₂CO₃; when the doping element source is K, the K source can be one or more of KOH and K₂S.

[0088] In some embodiments, in the first sintering treatment described above, the temperature is 400-600℃, the heating rate is 1-6℃ / min, and the holding time is 4-8h; in the second sintering treatment, the temperature is 800-1100℃, the heating rate is 1-5℃ / min, and the holding time is 10-15h.

[0089] Furthermore, in the first sintering treatment, the temperature is 600℃, the heating rate is 5℃ / min, and the holding time is 5h; in the second sintering treatment, the temperature is 900℃, the heating rate is 2℃ / min, and the holding time is 10h.

[0090] In this invention, the first calcination treatment and the second calcination treatment can be carried out under an inert atmosphere. This invention does not specifically limit the inert atmosphere. For example, the inert atmosphere can be selected from one or more of nitrogen, argon, helium and neon.

[0091] The method for preparing the composite cathode material of the present invention can produce the above-mentioned composite cathode material, and the preparation method is simple and suitable for widespread application.

[0092] In this invention, the process parameters for the first calcination treatment and the second calcination treatment can be further selected in order to better form the composite cathode material and improve the overall performance of the composite cathode material.

[0093] In some embodiments of the present invention, in the first calcination treatment, the temperature is 650-900℃, the heating rate is 1-5℃ / min, and the time is 2-12h; and / or,

[0094] In the second calcination process, the temperature is 100-200℃, the heating rate is 1-5℃ / min, and the time is 0.5-12h.

[0095] Furthermore, in the first calcination treatment, the temperature is 700℃, and the heating rate is 2℃ / min; and / or,

[0096] In the second calcination process, the temperature was 155℃ and the heating rate was 2℃ / min.

[0097] A third aspect of the present invention provides a battery comprising the composite cathode material described above.

[0098] In this invention, a positive electrode sheet can be prepared using the above-mentioned positive electrode material, and then a battery can be prepared using the positive electrode sheet containing the above-mentioned positive electrode material.

[0099] In some embodiments, the preparation process of the positive electrode sheet includes: mixing composite positive electrode material, conductive agent, solvent and binder to obtain positive electrode slurry, depositing the positive electrode slurry on at least one functional surface of the positive electrode current collector, and drying to obtain a positive electrode sheet containing a positive electrode active layer.

[0100] The battery of the present invention, due to including the above-mentioned composite cathode material, has excellent discharge specific capacity, cycle performance and safety performance.

[0101] The technical solution of the present invention will be further explained and described below with reference to specific embodiments.

[0102] Example 1

[0103] The battery in this embodiment is prepared by a method including the following steps:

[0104] 1. Preparation of composite cathode materials

[0105] 1) Sodium carbonate, nickel oxide, iron(III) oxide, manganese(III) oxide, and zinc oxide were mixed uniformly in a molar ratio of Na:Ni:Fe:Mn:Zn = 0.96:0.22:0.22:0.41:0.16, and then sintered at 930℃ for 12 h at a heating rate of 2℃ / min to obtain the positive electrode active material Na. 0.96 Ni 0.22 Fe 0.22 Mn 0.41 Zn 0.15 O2;

[0106] 2) The positive electrode active material and sucrose are mixed evenly at a mass ratio of positive electrode active material to carbon element of 1:0.05, and subjected to a first calcination treatment under an inert atmosphere to obtain an intermediate positive electrode material including a carbon coating layer, denoted as C@Na. 0.96 Ni 0.22 Fe 0.22 Mn 0.41 Zn 0.15 O2;

[0107] In the first calcination treatment, the temperature was 700℃, the time was 5h, and the heating rate was 2℃ / min.

[0108] The average pore size of the surface pores in the carbon coating is 80 nm, and the thickness of the carbon coating is 50 nm.

[0109] 3) The intermediate cathode material and sublimed sulfur are mixed uniformly at a carbon to sulfur mass ratio of 1:1, and then subjected to a second calcination treatment under an inert atmosphere to obtain the composite cathode material, denoted as C / S@Na. 0.96 Ni 0.22 Fe 0.22 Mn 0.41 Zn 0.15 O2;

[0110] In the second calcination treatment, the temperature was 155℃, the time was 12h, and the heating rate was 2℃ / min.

[0111] Figure 1 The image shown is a SEM image of the composite cathode material in Example 1 of this invention. Figure 1 It can be seen that the surface of the composite cathode material of the present invention has particulate matter (which can be regarded as a carbon coating layer).

[0112] 2. Battery manufacturing

[0113] The composite cathode material, Ketjen black and PVDF binder were mixed in a mass ratio of 92:4:4, and an appropriate amount of NMP solution was added to form a cathode slurry. The cathode slurry was coated on two functional surfaces of an aluminum foil, dried, and then baked in a vacuum oven at 120°C for 12 hours to obtain a cathode sheet.

[0114] A positive electrode, a separator, and a sodium metal negative electrode are stacked to obtain an electrode assembly. The electrode assembly is placed in an outer package, and an electrolyte is injected into the outer package to obtain a half cell.

[0115] The electrolyte includes NaClO4, EC, and EMC, with a volume ratio of EC to EMC of 3:7 and a NaClO4 concentration of 1 mol / L.

[0116] Example 2

[0117] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0118] In the preparation of the composite cathode material, the sublimated sulfur in step 3) is replaced with selenium powder, and the carbon and selenium are mixed uniformly at a mass ratio of 1:1. A second calcination treatment is then performed under an inert atmosphere to obtain the composite cathode material, denoted as C / Se@Na. 0.96 Ni 0.22 Fe 0.22 Mn 0.41 Zn 0.15 O2.

[0119] Example 3

[0120] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0121] In the preparation of the composite cathode material, in step 2), the mass ratio of the cathode active material to carbon element is 1:0.02, and the thickness of the carbon coating layer is 20 nm.

[0122] Example 4

[0123] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0124] In the preparation of composite cathode materials, in step 3), the mass ratio of carbon to sulfur is 1:0.5.

[0125] Example 5

[0126] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0127] In the preparation of composite cathode materials, in step 3), the mass ratio of carbon to sulfur is 1:1.5.

[0128] Example 6

[0129] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0130] In the preparation of composite cathode materials, in step 3), the mass ratio of carbon to selenium is 1:0.5.

[0131] Example 7

[0132] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0133] In the preparation of composite cathode materials, in step 3), the mass ratio of carbon to selenium is 1:1.5.

[0134] Example 8

[0135] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0136] In the preparation of the composite cathode material, in step 3), the intermediate cathode material and sublimated sulfur and selenium powder are subjected to a second calcination treatment under an inert atmosphere at a mass ratio of carbon, sulfur, and selenium of 1:0.5:0.5 to obtain the composite cathode material, denoted as C / (S,Se)@Na. 0.96 Ni 0.22 Fe 0.22 Mn 0.41 Zn 0.15 O2.

[0137] Example 9

[0138] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0139] In the preparation of composite cathode materials, in step 3), the mass ratio of carbon, sulfur and selenium is 1:1:0.5.

[0140] Example 10

[0141] The battery preparation method in this embodiment is basically the same as that in Example 8, except that:

[0142] In the preparation of the composite cathode material, in step 2), the mass ratio of the cathode active material to carbon element is 1:0.02, and the thickness of the carbon coating layer is 20 nm.

[0143] Example 11

[0144] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0145] 1. Preparation of composite cathode materials

[0146] Step 1) Mix the nickel-cobalt-manganese transition metal carbonate precursor and lithium carbonate in a molar ratio of Li:Ni:Co:Mn = 1:0.9:0.05:0.03, perform the first sintering treatment, and cool to room temperature to obtain the intermediate positive electrode active material;

[0147] After grinding and mixing the intermediate positive electrode active material with Al2O3 until uniform, a second sintering treatment is performed, followed by cooling to room temperature to obtain the positive electrode active material, denoted as LiNi. 0.90 Co 0.05 Mn 0.03 Al 0.02 O 2.015 ;

[0148] In the first sintering treatment, the temperature was 600℃, the heating rate was 6℃ / min, and the holding time was 4h; in the second sintering treatment, the temperature was 900℃, the heating rate was 1.5℃ / min, and the holding time was 10h.

[0149] The intermediate cathode material in step 2) is denoted as C@LiNi 0.90 Co 0.05 Mn 0.03 Al 0.02 O 2.015 ;

[0150] The composite cathode material in step 3) is denoted as C / S@LiNi 0.90 Co 0.05 Mn 0.03 Al 0.02 O 2.015 ;

[0151] In the second calcination treatment, the temperature was 155℃, the time was 12h, and the heating rate was 2℃ / min.

[0152] 2. Battery manufacturing

[0153] A positive electrode, a separator, and a lithium metal negative electrode are stacked to obtain an electrode assembly. The electrode assembly is placed in an outer package, and an electrolyte is injected into the outer package to obtain a half cell.

[0154] The electrolyte includes LiF6, EC and EMC, with a volume ratio of EC to EMC of 3:7 and a concentration of LiF6 of 1 mol / L.

[0155] Example 12

[0156] The battery preparation method in this embodiment is basically the same as that in Example 11, except that:

[0157] In the preparation method of the composite cathode material, the sublimed sulfur in step 3) is replaced with selenium powder, and the carbon and selenium elements are mixed evenly at a mass ratio of 1:1. A second calcination treatment is then performed under an inert atmosphere to obtain the composite cathode material, denoted as C / Se@LiNi. 0.90 Co 0.05 Mn 0.03 Al 0.02 O 2.015 .

[0158] Example 13

[0159] The battery preparation method in this embodiment is basically the same as that in Example 11, except that:

[0160] In the preparation method of the composite cathode material, in step 3), the intermediate cathode material and sublimated sulfur and selenium powder are subjected to a second calcination treatment under an inert atmosphere at a mass ratio of carbon, sulfur and selenium of 1:0.5:0.5 to obtain the composite cathode material, denoted as C / (S,Se)@LiNi. 0.90 Co 0.05 Mn 0.03 Al 0.02 O 2.015 .

[0161] Example 14

[0162] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0163] In the preparation of the composite cathode material, in step 2), the mass ratio of the cathode active material to carbon element is 1:0.2, and the thickness of the carbon coating layer is 200 nm.

[0164] Example 15

[0165] The battery preparation method in this embodiment is basically the same as that in Example 1, except that:

[0166] In the preparation of composite cathode materials, in step 3), the mass ratio of carbon to sulfur is 1:4.

[0167] Comparative Example 1

[0168] The preparation method of the battery in this comparative example is basically the same as that of the battery in Example 1, except that:

[0169] Batteries were prepared using the positive electrode active material prepared in Example 1 as the positive electrode material.

[0170] Comparative Example 2

[0171] The preparation method of the battery in this comparative example is basically the same as that of the battery in Example 1, except that:

[0172] A battery was prepared using the intermediate cathode material prepared in Example 1 as the cathode material.

[0173] Comparative Example 3

[0174] The preparation method of the battery in this comparative example is basically the same as that of the battery in Example 11, except that:

[0175] A battery was prepared using the positive electrode active material prepared in Example 11 as the positive electrode material.

[0176] Comparative Example 4

[0177] The preparation method of the battery in this comparative example is basically the same as that of the battery in Example 11, except that:

[0178] The intermediate cathode material prepared in Example 11 was used as the cathode material to prepare the battery.

[0179] Performance testing

[0180] 1. Impedance test and surface moisture test were performed on the composite cathode material in the example and the cathode material in the comparative example, respectively. The test results are shown in Table 1. The impedance test was performed using an MCP-PD51 powder impedance tester. The test conditions were 4-5g sample amount and 5.03KN test pressure. The specific test method refers to GB / T 30835-2014.

[0181] The surface moisture test was conducted using an 831 calorimeter. The test conditions included a sample size of 0.5-1.5g, ambient humidity ≤30%, air flow rate of 40-50ml / min, and heating temperature of 100℃. For specific test methods, refer to GB / T11133-2015.

[0182] 2. The first discharge specific capacity and cycle capacity retention rate of the batteries in the examples and comparative examples were tested respectively. The test results are shown in Table 1.

[0183] The test methods for initial discharge specific capacity and cycle capacity retention are as follows:

[0184] For sodium-ion batteries, a constant current charge / discharge mode is used at 0.1C (17 mAg). -1 Under the voltage window of 2 to 4.2V, the battery charge and discharge tests were conducted to obtain the battery's first discharge specific capacity and capacity retention rate after 20 cycles.

[0185] For lithium-ion batteries, a constant current charge / discharge mode is used at 0.1C (20 mAg). -1 Under the voltage window of 2.5 to 4.25V, the battery charge and discharge tests were conducted to obtain the battery's first discharge specific capacity and capacity retention rate after 20 cycles.

[0186] Table 1

[0187]

[0188]

[0189] As can be seen from Table 1, the battery in the embodiments of the present invention has both excellent capacity retention rate and discharge specific capacity.

[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite cathode material, characterized in that, Includes a core and a carbon coating covering at least a portion of the surface of the core; The core is a positive electrode active material, the carbon coating layer includes elemental sulfur and / or elemental selenium, and the surface of the carbon coating layer has pores, and the thickness of the carbon coating layer is 1-200 nm. After pre-discharge, the carbon coating layer of the composite cathode material includes Me2S. x and / or Me2Se x ; Where Me is selected from Li or Na, and 1≤X≤8; The surface moisture content of the composite cathode material is 90-700 ppm; Based on the total mass of the composite cathode material, the carbon coating layer has a mass percentage content of 0.5-15%. The mass ratio of the sulfur and / or the selenium to the carbon in the carbon coating layer is (1:10)-(3:1).

2. The composite cathode material according to claim 1, characterized in that, If Me is Na, then the positive electrode active material has the molecular formula shown in Formula 1; Na b1 Ni c1 Fe d1 Mn e1 M f1 O g1 Formula 1; In Equation 1, c1+d1+e1+f1=1, 0.67≤b1≤1.25, 0.15≤c1≤0.35, 0.15≤d1≤0.35, 0.25≤e1≤0.66, 0.15≤f1≤0.35, and M is a dopant element.

3. The composite cathode material according to claim 1, characterized in that, If Me is Li, the positive electrode active material has the molecular formula shown in Formula 2; Li b2 Ni c2 Co d2 Mn e2 L f2 O g2 Formula 2; In Equation 2, c2+d2+e2+f2=1, 0.75≤b2≤1.45, 0.6≤c2≤0.95, 0.005≤d2≤0.2, 0.005≤e2≤0.2, 0≤f2≤0.02, and L is the dopant element.

4. The composite cathode material according to any one of claims 1-3, characterized in that, The pore size is 0.1-100 nm.

5. A method for preparing the composite cathode material according to any one of claims 1-4, characterized in that, Includes the following steps: A first calcination treatment is performed on a first mixed system including positive electrode active material and carbon source to obtain intermediate positive electrode material; The intermediate cathode material is mixed with a sulfur source and / or a selenium source to obtain a second mixed system, and the second mixed system is subjected to a second calcination treatment to obtain the composite cathode material.

6. The preparation method according to claim 5, characterized in that, In the first calcination treatment, the temperature is 650-900℃, the heating rate is 1-5℃ / min, and the time is 2-12h; and / or, In the second calcination treatment, the temperature is 100-200℃, the heating rate is 1-5℃ / min, and the time is 0.5-12h.

7. A battery, characterized in that, Includes the composite cathode material as described in any one of claims 1-4.

Citation Information

Patent Citations

  • Sodium-selenium battery positive electrode material and preparation method thereof

    CN111342016A

  • Carbon-coated lithium-containing transition metal phosphate cathode material and preparation method thereof

    CN111342018A

  • Low-temperature vapor deposition coated high-nickel ternary layered positive electrode material and preparation method thereof

    CN112768662A